PC.127 Using immersive simulation as a learning tool for neonatal specialist medical trainees and nursing staff. (9th June 2014) - Peirce, E; Lok, A; Moore, H; Ahmed, A; Shore, H; Clark, S
Abstract : Simulation is already becoming an integral part of medical training and of assessment of competencies. Initially the majority of simulation has been based on individual case simulation, concentrating on clinical knowledge and practical skills. In the Yorkshire and Humber deanery immersive simulation was introduced in 2011 to support transition of paediatric SHOs to registrar level. It involved a 4-bedded simulated ward and theatre. Immersive simulation allows for a more realistic approach, where ward round, prioritisation, decision-making and multi-disciplinary skills can all being assessed. This allows for an emphasis on human-factors and communication skills to be developed in a way that small scale simulation cannot achieve. Within the deanery's simulation strategy it was recognised that there was limited simulation being offered to neonatal trainees. We proposed to initiate an immersive simulation course for this group of trainees. This would be made up of a 4-bedded simulated neonatal intensive care unit and resuscitation bay. However, using immersive simulation in this setting is a more complex process. Challenges we faced were; availability of further equipment, for example incubators and ventilators; the ability to use these in conjunction with mannequins and the integration of nursing staff to the simulation. We present the process that we went through in order to set up regional immersive neonatal simulation for trainees on the neonatal grid and those with a special interest. We comment on the inclusion of nursing candidates along side medical candidates. We discuss the challenges we faced and the solutions that worked in our setting.